The significance of the actual sentence between negation and affirmation in the hanging of Al-Nabigha Al-Dhubyani - Muzafaraddin Othman Hamadsalih; Esmael Hamed Hamad Ameen (Zanco Journal of Humanity Sciences)
This research is an attempt to study (the significance of the actual sentence between negation and affirmation in the hanging of Al-Nabigha Al-Dhibyani) in a grammatical and applied semantic framework for the purpose of identifying the patterns of the actual sentence structure and its structural forms in its hanging and its implications. Because the actual sentence is important, and there is a lot of rotation in Arabic speech, and the speaker does not dispense with it in his speech, because it expresses the things surrounding him and understands with others; Because it is one of the two parts of the sentences in Arabic, and the other part is the nominal sentence, and the nature of the research required dividing it into three sections. The first topic deals with the significance of the affirmed verb sentence that has no place in the parsing, while the second topic studies the actual affirmed sentence that has a place in the parsing, while the last topic is devoted to studying the negative actual sentence, and the research ends with the most important results that the research reached. The research followed the descriptive analytical method to study the verses of the hanging.